A comparative study on Acorus calamus (Acoraceae) micropropagation and selection of suitable population for cultivation in Iran - Gholipour, Abbas; Kazemitabar, Seyed Kamal; Ramzanpour, Hamed (Acta Biologica Szegediensis, 2021)
In addition to various medicinal properties, Acorus calamus (sweet ﬂag) is used in health, food, and perfume industries. Since this species is a rare plant in Iran, its propagation and cultivation are of the great importance. The aim of this study was to investigate the effects of different plant growth regulators on micropropaga-tion of this plant and to select the appropriate population. The root, the rhizome and the leaf explants of three populations (Arzefon, Pelesk, and Alandan) were cultured on MS medium supplemented with different concentrations of α-naphthalene acetic acid (NAA) and 6-benzylaminopurine (BAP) for callus induction and plant regeneration. The results showed that only rhizome explant resulted in direct plant regeneration. Among different treatments, the 1 mg/l treatment of BAP and NAA - with the highest mean number of regenerated plants (3.75 ± 0.85), the highest percentage of grown explants (91.6%) and maximum average length of regenerated plants (12.06 ± 0.32 cm) - was the best treatment for regeneration of sweet ﬂag. The highest mean number of root (6.6 ± 0.1) was observed in Alandan population in 1 mg/l treatment of indole-3-butyric acid (IBA). According to the present study, Alandan population is suitable for cultivation purposes in Iran.